Problems of recognition and implementation of legal mechanisms for the implementation of the right to same-sex marriage in the world (comparative legal aspect) - Rosoliak, Oksana; Yednak, Oleksandr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article raises issues of recognition and implementation of legal mechanisms for the implementation of the right to same-sex marriage in legislative acts and other sources of law of foreign countries. The authors emphasize that same-sex marriage is a serious challenge for the world community and a driving force for changing traditional patterns of thinking. However, in order to rationalize public opinion, the first step is to take the necessary measures to overcome discrimination against the LGBT community